Event marketing : how to successfully promote events, festivals, conventions, and expositions - Preston, Chris , 1961- (Wiley event management series, 2012)
A modern, completely updated guide to effective event marketing As the events market becomes increasingly saturated, it is essential for a successful event professional to understand the use of strategic marketing plans. Events are everywhere--in the U.S